Development of Mini Scale Automatic Portable Lifter for Luggage in Kolej Kediaman Pagoh Universiti Tun Hussein Onn Malaysia - Suhaimin, Syamil; Harun, Dalila; Sadun, Amirul (Progress in Engineering Application and Technology, 2023)
The final year project aimed to develop a prototype for an automatic portable lifter to transport students’ belongings in public buildings. The problem addressed was the deficiency of elevators in government buildings makes it difficult for students, as many of them carry a lot of belongings to college. The objective was to design and develop a model-size portable automatic lifting system that could be easily implemented into these buildings without being permanently attached, and to analyse its performance in terms of practicality and reliability. The solution proposed was a pulley system with an electrical DC motor and motor driver, as well as a proximity sensor to control the movement of the cart. The control system used was a NodeMCU ESP32, connected to a Bylink IoT system as a pushbutton. The prototype was powered by a 12V battery, which was charged using a 100-watt solar panel. Testing included function tests, load tests, practicality tests, and solar charging rate tests. Results showed that the prototype was successful in its movement but had some problems. A load of 5 kg was found to be the limit for the prototype. Results of the practicality test showed that the prototype could run for 8 cycles with different loads but had some problems. Finally, the solar charging rate test showed that it took 2 hours for the 12V battery to fully charge.